Education-Occupation Mismatch and the Role of Internal Migration Streams in Shaping Returns to Education - Mahmood, Farrukh; Rana, Abdul Wahab (Asian Journal of Applied Economics, 2026)
Background and Objectives: Education is a primary pillar of human capital development, directly impacting labor market performance and economic growth. While global returns to education are increasing, the Pakistani labor market continues to face significant inefficiencies in the form of education-occupation mismatch (EOM), where individual skills fail to align with job demands. Literature suggests that nearly 45% of the Pakistani workforce experieces such mismatches, resulting in wage penalties, skill underutilization, and reduced productivity. This study examines the returns to education and EOM through the lens of internal migration. By integrating job-matching theory with migration economics, this paper hypothesizes that migration to diverse labor markets reduces the negative outcomes of employment mismatch and improves the distribution of match quality. Methodology: The study utilizes the Pakistan Social and Living Standards Measurement (PSLM) 2019-20 survey, focusing on a refined sample of 114,586 household heads aged 15 to 65. The education-occupation fit is determined via the realized-matches approach, calculating the mean and standard deviation of education levels within four-digit occupational groups to identify overeducated, undereducated, and matched individuals. The empirical analysis employs an augmented Mincer equation to estimate returns to education. To address inflated variance and measurement errors in logarithmic monthly wages, the study utilizes advanced statistical learning models, including Ridge, Lasso, and Elastic Net regressions, with 10-fold cross-validation and 100 bootstrap replications. To mitigate endogeneity and omitted-variable bias, an instrumental-variables (IV) framework with a two-step least-squares estimator is applied, using family educational background as a valid instrument. Key Findings: The empirical results yield three primary findings regarding the Pakistani labor market. First, educational returns are significant, with earnings increasing at a rate of 14.9% for each additional year of schooling after controlling for endogeneity. Second, the analysis reveals a concave relationship between education-occupation mismatch and earnings, wherein under-educated individuals face a substantial wage penalty of 18.2% compared to their adequately educated counterparts, while over-educated individuals experience diminishing marginal returns with income increases of only 7.68%. Third, internal migration exerts a transformational effect, as migrants on average earn more than non-migrants. Specifically, migration streams—particularly rural-to-urban and urban-to-urban flows—redefine educational returns and flatten the mismatch returns curve, thereby reducing wage inefficiencies caused by skill imbalances. Policy Implications: Maximizing economic returns on human investment in Pakistan requires a multi-layered intervention. It is necessary to enhance vocational guidance and align educational curricula with market demands to reduce early-career mismatch penalties. Furthermore, policies should facilitate internal mobility to various urban labor markets to mitigate the wage inefficiencies identified in the study. Targeted measures are also required to address the severe wage penalties faced by married women, including promoting female entrepreneurship within independent contracting and agriculture, ensuring pay equity, and enhancing workplace inclusivity. Ultimately, achieving equitable labor market outcomes requires dismantling the structural and normative barriers that currently limit the career progression of the female workforce.